A review of Pseudolechriops Champion (Coleoptera: Curculionidae: Conoderinae) - Hespenheide, Henry A.; Lapierre, Louis M. (Zootaxa, 2006)
Nine new species are described in the formerly monotypic genus Pseudolechriops Champion: P. longinoi, new species; P. dimorpha, new species; P. howdenorum, new species; P. davidsonae, new species; P. klopferi, new species; P. janeae, new species; P. alleni, new species; P. wrightae, new species; P. coleyae, new species. These species can be separated into two groups, the megacephala